Derivación de verbos de cambio en el aimara: -pta y -ra - Gonzalo Segura, Roger (2018)
The article consists of a detailed description from Jackendoff’s Conceptual Semantics of two denominative suffixes that have the property of deriving verbs of change or becoming from the southern Aymara: the -pta absolute state change and the -ra gradual state change.